2018
DOI: 10.1021/acsami.8b03777
|View full text |Cite
|
Sign up to set email alerts
|

Ultralight Microcellular Polymer–Graphene Nanoplatelet Foams with Enhanced Dielectric Performance

Abstract: Dielectric polymer nanocomposites with high dielectric constant (ε') and low dielectric loss (tan δ) are extremely desirable in the electronics industry. Percolative polymer-graphene nanoplatelet (GnP) composites have shown great promise as dielectric materials for high-performance capacitors. Herein, an industrially-viable technique for manufacturing a new class of ultralight polymer composite foams using commercial GnPs with excellent dielectric performance is presented. Using this method, the high-density p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(46 citation statements)
references
References 69 publications
2
44
0
Order By: Relevance
“…Similar high electrical conductivity of conductive polymer composite foams was also found in some other published literatures . Moreover, it is reported that there is an optimal expansion ratio to allow the nanocomposite foams with a fixed MWCNT content to achieve the highest electrical conductivity . However, the optimal expansion ratio is very low, usually less than fivefold.…”
Section: Resultssupporting
confidence: 85%
“…Similar high electrical conductivity of conductive polymer composite foams was also found in some other published literatures . Moreover, it is reported that there is an optimal expansion ratio to allow the nanocomposite foams with a fixed MWCNT content to achieve the highest electrical conductivity . However, the optimal expansion ratio is very low, usually less than fivefold.…”
Section: Resultssupporting
confidence: 85%
“…This was due to an increase in the number of "micro-capacitors" and the increased interface between rGB and SR; this resulted in higher interfacial polarization density and dielectric constant. 11 Therefore, the sample obtained using the rGO volume fraction of 0.81 vol% at the frequency of 1 kHz had the ultrahigh dielectric constant of up to 2.71 Â 10 4 , which was four orders of magnitude higher than that of the MS/SR composite. In particular, note that both MS/rGO/SR and MS/borate/SR have signicantly lower dielectric constants than the MGS composite; this shows that a synergistic effect exists between rGO and borates with an increase in dielectric constants.…”
Section: Dielectric Property Of Mgsmentioning
confidence: 90%
“…10 Polymer-based conductive ller composites have the advantages of lightweightness, low cost, high exibility, high corrosion resistance, excellent processability, and adjustable dielectric constant and dielectric loss. 11 To a certain extent, these advantages overcome the limitations of polymerbased ceramic ller composites and can help in the achievement of higher dielectric constants at ultralow ller concentrations; 6,12,13 therefore, these composites have broad application prospects in health monitoring, wearable electronic devices, motion sensors and electromagnetic shielding. [14][15][16] The conductive network formed by conductive llers can usually improve the electrical properties of composites.…”
Section: Introductionmentioning
confidence: 99%
“…After rapid pressure reduction, CO 2 solubility in a composite decreases, causing nucleation and growth of oversaturated CO 2 to generate bubbles. [125] The GNP had nominal dimensions of 50 µm in diameter and 20 nm in thickness. Such porous structures encompass closed cell pores, open-cell pores (interconnected cells), macropores, and mesopores.…”
Section: Supercritical Foamingmentioning
confidence: 99%
“…As a result, 2D nanosheets coated with a porous polymer network are formed. [125] This foaming action resulted in a positive synergistic effect to produce parallel GNPs that were very polarizable in applied fields. Foam inner morphology relies on SCF saturation level that is associated with several parameters such as SCF pressure and temperature, dynamics of nucleation and bubble growth (due to pressure drop and interfacial stabilization by nanosheets [126] ), and SCF pressure reduction rate.…”
Section: Supercritical Foamingmentioning
confidence: 99%